2007
DOI: 10.2754/avb200776010051
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between Somatic Cell Count and Acute Phase Proteins in Serum and Milk of Dairy Cows

Abstract: The aim of the present study was to compare the concentrations of two acute phase proteins, haptoglobin (Hp) and serum amyloid A (SAA), in serum and milk of Holstein-Friesian dairy cows grouped according to somatic cell count thresholds (< 100,000 < 400,000 > 400,000 cells/ml) in composite milk samples. The SCC was assessed quantitatively by FOSSOMATIC 90 analyser; serum and milk Hp and SAA concentrations were determined using commercial ELISA kits (Tridelta Development, Ltd., Wicklow, Ireland). We have found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
1
12
0
8
Order By: Relevance
“…It has been reported that monitoring the plasma concentration of acute phase proteins, such as SAA and Hp, provides a valuable diagnostic information on cattle conditions (Eckersall 2000), to discriminate between cattle with acute and sub-clinical or chronic respiratory diseases (Godson et al 1996) and to detect cows with clinical mastitis (Eckersall et al 2001). Kováč et al (2007) reported also that the measurements of the acute phase proteins, haptoglobin and serum amyloid A, predominantly in milk, may be useful in monitoring udder health. In general, the time around calving is considered to be a critical period with a negative impact on the energy and protein metabolism (Kováč 2001).…”
mentioning
confidence: 99%
“…It has been reported that monitoring the plasma concentration of acute phase proteins, such as SAA and Hp, provides a valuable diagnostic information on cattle conditions (Eckersall 2000), to discriminate between cattle with acute and sub-clinical or chronic respiratory diseases (Godson et al 1996) and to detect cows with clinical mastitis (Eckersall et al 2001). Kováč et al (2007) reported also that the measurements of the acute phase proteins, haptoglobin and serum amyloid A, predominantly in milk, may be useful in monitoring udder health. In general, the time around calving is considered to be a critical period with a negative impact on the energy and protein metabolism (Kováč 2001).…”
mentioning
confidence: 99%
“…Hp is commonly used in monitoring the treatment of limb diseases (Jawor et al 2008) and the health of the udder (Kováč et al 2007), detecting diseases of clinical or subclinical course in calves, and in monitoring herd health (Ganheim et al 2003). The broad availability of Hp in cattle diagnostics has resulted in this APP becoming the most commonly determined in this species.…”
mentioning
confidence: 99%
“…Hirvonen et al (1996Hirvonen et al ( , 1999 and Ohtsuka et al (2001) have described increased haptoglobin concentration in cow serum. Kováč et al (2007) recommend determining acute phase proteins (haptoglobin and SAA) in serum, and also in milk, as a useful tool for diagnostics of mastitis and possible indicator of milk quality.…”
mentioning
confidence: 99%